Recent Advances in Non-invasive Brain Stimulation for Major Depressive Disorder - Liu, Shui; Sheng, Jiyao; Li, Bingjin; Zhang, Xuewen (Frontiers in Human Neuroscience, 2017)
Non-invasive brain stimulation (NBS) is a promising treatment for major depressive disorder (MDD), which is an affective processing disorder involving abnormal emotional processing. Many studies have shown that repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) over the prefrontal cortex can play a regulatory role in affective processing. Although the clinical efficacy of non-invasive brain stimulation in MDD has been demonstrated clinically, the precise mechanism of action remains unclear. Therefore, data were collected from Web of Science, Medline, PubMed, through searching of these keywords: “major depressive disorder”, “non-invasive Brain Stimulation”, “repetitive transcranial magnetic stimulation”, “transcranial direct current stimulation” and “affective processing”. This review summarizes the current status of NBS methods, including rTMS and tDCS, in the treatment of MDD. The article explores possible correlations between depressive symptoms and affective processing, highlighting the relevant affective processing mechanisms. Our review provides a reference for the safety and efficacy of NBS methods in the clinical treatment of MDD.